Sexual Harassment AND Its effects on Mental Health OF THE Teenage School Girls in Lalitpur and rupandehi district - Dr. Kalpana Gyawali (Journal of Balkumari College, 2022)
A cross-sectional study was conducted to find the prevalence of mental health on teenage girl students and the effect of sexual harassment on their mental health: depression, anxiety, and stress. A concurrent mixed method was used and the study was conducted at both community and institutional schools of Lalitpur and Rupendehi districts. A semi-structured questionnaire was used for quantitative data collection along with DASS (42 points) test to measure depression, anxiety, and depression. Focus group discussion (FGD), in-depth interviews (IDI), and key informant information (KII) were used for qualitative data collection. Poor and ill mental health were found among the respondents and the prevalence of depression, anxiety and stress were 45%, 52%, and 35% respectively among the sexually harassed girl. As sexual harassment was found as one of the major factors that responsible for the poor mental health status of girl students, it is necessary for every school to adopt anti-sexual harassment policies and to take action against it to create a healthy learning environment.